TRPM7 kinase activity is essential for T cell colonization and alloreactivity in the gut - Romagnani, Andrea; Vettore, Valentina; Rezzonico-Jost, Tanja; Hampe, Sarah; Rottoli, Elsa; Nadolni, Wiebke; Perotti, Michela; Meier, Melanie A.; Hermanns, Constanze; Geiger, Sheila; Wennemuth, Gunther; Recordati, Camilla; et al. (Nature Communications, 2017)
The melastatin-like transient-receptor-potential-7 protein (TRPM7), harbouring a cation channel and a serine/threonine kinase, has been implicated in thymopoiesis and cytokine expression. Here we show, by analysing TRPM7 kinase-dead mutant (Trpm7 R/R ) mice, that the enzymatic activity of the receptor is not essential for thymopoiesis, but is required for CD103 transcription and gut-homing of intra-epithelial lymphocytes. Defective T cell gut colonization reduces MHCII expression in intestinal epithelial cells. Mechanistically, TRPM7 kinase activity controls TGF-β-induced CD103 expression and pro-inflammatory T helper 17, but not regulatory T, cell differentiation by modulating SMAD2. Notably, we find that the TRPM7 kinase activity promotes gut colonization by alloreactive T cells in acute graft-versus-host disease. Thus, our results unravel a function of TRPM7 kinase in T cell activity and suggest a therapeutic potential of kinase inhibitors in averting acute graft-versus-host disease.
CRIS-Team Scopus Importer:2024-07-10